Stress profile of students of the University of the Philippines College of Dentistry - Salvacion, Maria Lourdes Dorothy S. (2004)
This study aimed to come up with the Stress Profile of the Students of the University of the Philippines, College of Dentistry (UPCD). Due to the increasing attrition rate of the UPCD, studies have been undertaken to try to identify problems and possible solutions to such a complex phenomenon. One such study is the present study on stress. One hundred and forty nine out of two hundred and five enrolled students completed three questionnaires: a Modified Dental Environment Stress Questionnaire (DESQ), the Personal Stress Profile Questionnaire (PSPQ), and in-depth questionnaire with open-ended questions. Small group discussions were also conducted. Results of the DESQ showed that academic and clinical requirements were the top stressors for the UPCD dental students. Academic factors were the most stressful for the first 3 year levels. The peak of academic stress was during the sophomore year. The upper year levels rated clinical requirements as the top stressors. Among the most stressful individual stressful events were: (1) Examinations and Grades, (2) Fully loaded days, (3) Difficulty completing clinical requirements, and (4) Fear of getting delayed. Significant differences were noted in the ranking for faculty and clinical requirements among the different year levels, clinical status, and number of years in the college. No significant difference in ranking was observed between the genders. Results of the PSPQ revealed that there was an undeniable similarity in the general stress profiles of the different year levels. About 50-60% of each class reported high vulnerability, 30-40% low vulnerability, and remainder (a minority of 10-20%) of moderate vulnerability. The students showed high vulnerability to the psychosocial process of frustration and overload. The ratings for these two factors manifested significant differences across the year levels and years of stay in the UPCD. No significant difference was observed between gender and clinical status. Common methods of coping employed by the students were: crying, praying, talking, watching movies, listening to music. As the year level increased there was an observable decrease in optimism regarding their ability to cope with the stress of dental education. Based on the material gathered the alternative hypothesis was accepted, that there were significant differences in the stress profile of the students of the UPCD according to year level, number of years in the program, and clinical status. In the case of gender, however, the null hypothesis was accepted - that there were no significant differences in the perception of stress among the students of UPCD according to gender. The influence of environmental factors predominated in both the external sources and internal causes of stress. The top sources of stress identified were academic and clinical requirements. Seemingly related to this were the ratings given to Faculty. The top psycho-physiological causes of stress were frustration and overload, both psychosocial causes of stress. They were primarily reactions to external stressful stimuli, namely academic and clinical requirements as compounded by relations with the faculty. These were perceived stressful because of the student's lack of control over them. The results of this study bring a lot of hope, because the factors identified are precisely within the control of the school. The external forces acting upon the students (academic and clinical requirements, faculty relations, etc.) are the domain of the school. The administration and faculty have the mandate and the responsibility to create that environment which can challenge and inspire the students, providing those (external) opportunities which make (internal) learning possible. Now that the stress profile has been drawn up, the college authorities can focus their efforts into building the conducive learning environment, characterized by the predominance of eustress instead of distress. The recommendations arising from study are two-pronged. One line of recommendations focuses on the object or matter of the stress factors identified in the study. These recommendations include matters requiring curricular review (sequencing, evaluation methods, academic and clinical requirements) as well as suggestions for faculty development (lectures/seminars on teaching styles, standardization of clinical evaluation criteria, test construction, motivation theories, etc.) The other line of recommendations include the establishment of systems for the early identification and assistance for the highly vulnerable students.
Major project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: College of Dentistry. University of the Philippines; Stress; Dental students